Mekanisme Jalannya Mediasi Penyelesaian Sengketa Tanah di Pengadilan Negeri Semarapura (Studi Kasus Putusan Pengadilan Negeri Semarapura Nomor 53/Pdt.G/2022/PN Srp) - I Gede Artana; Deli Bunga Saravistha (Indra Institute Research & Publication, 2023)
Land dispute settlement mechanisms are classified as civil settlements. To overcome the accumulation of case files, the Supreme Court has issued Supreme Court Regulation Number 1 of 2016 concerning Mediation in Courts or commonly known as Judicial Mediation. Around 36,771 court decisions were recorded on land cases that were handled through litigation, this shows the high number of disputes that questioned land as an object. There were 166 appealed decisions to the High Court with details of 4 granted, 6 annulled, 68 upheld, 1 level I court decision which was unacceptable and 87 decisions entered into other records. These records are only reports in a district court in Denpasar, at the overall level of course the figure will be many times higher. Land Dispute Settlement Mechanism at the Semarapura District Court (Case Study of Semarapura District Court Decision Number 53/Pdt.G/2022/PN Srp)”. The objectives to be achieved are: 1. to add to the knowledge or insight of students, both readers and writers and all academics regarding the mechanisms for resolving land disputes at the Semarapura District Court (case study of Semarapura District Court Decision Number 53/Pdt.G/2022/PN Srp) . to find out the legal basis and aspects of resolving inherited land disputes at the Semarapura District Court (case study of Semarapura District Court Decision Number 53/Pdt.G/2022/PN Srp). The research method used is empirical juridical research method, namely research based on primary data as the main data source and secondary data as a complement. An interesting problem is to further analyze the success of the mediation process in the Semarapura District Court Decision Number 53/Pdt.G/2022/PN Srp) in accommodating the interests of the parties, so that even though it failed at least mediation played a role in helping to fulfill the elements of a consensus settlement which is national identity.